When the following quadratic equation is written in general form, what is the value of "c"?
-8
-6
-2

Question

Asked 11/26/2014 8:05:05 AM

Updated 11/26/2014 5:57:32 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/26/2014 5:57:32 PM]

s

Matanglawin|Points 82|

Question

Asked 11/26/2014 8:05:05 AM

Updated 11/26/2014 5:57:32 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/26/2014 5:57:32 PM]

Rating

8

x^2 + x - 12 = 0

x^2 + 4x - 3x - 4*3 = 0

(x + 4)(x - 3) = 0

(x + 4)(x - 3) = 0 is in factored form.

x^2 + 4x - 3x - 4*3 = 0

(x + 4)(x - 3) = 0

(x + 4)(x - 3) = 0 is in factored form.

Added 11/26/2014 5:50:09 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/27/2014 4:17:15 AM], Rated good by andrewpallarca

8

The following points of (-3, 21) lies on the graph of y = x^2 - 2x + 6.

When x = -3

y = (-3)^2 - 2*(-3) + 6

y = 9 + 6 + 6

y = 9 + 12

y = 21

When x = -3

y = (-3)^2 - 2*(-3) + 6

y = 9 + 6 + 6

y = 9 + 12

y = 21

Added 11/26/2014 5:51:44 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/27/2014 4:18:08 AM], Rated good by andrewpallarca

8

(x - 2)(x - 3) = 2

x^2 - 2x - 3x + 6 - 2 = 0

x^2 - 4x - x + 4 = 0

(x - 1)(x - 4) = 0

(x - 1)(x - 4) = 0 is in factored form .

x^2 - 2x - 3x + 6 - 2 = 0

x^2 - 4x - x + 4 = 0

(x - 1)(x - 4) = 0

(x - 1)(x - 4) = 0 is in factored form .

Added 11/26/2014 5:55:34 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/27/2014 4:19:15 AM], Rated good by andrewpallarca

Solve the inequality 8x - 10 > 7x + 20.
x -10
x 30 **Weegy:** 8x + 3 = 7x - 2 8x - 7x = -2 - 3 x = -5 **User:** Solve the inequality 7(x - 2) 9/7
x -9/7 **Weegy:** 7(x - 2) **User:** Solve the inequality 3(x + 1) + 2(x + 2) > 0.
x -7/5
x 7/5 **Weegy:** b.x > -7/5 of course. Please, rate the answer ?Good? and let us grow if you are satisfied. Thank you for the interest. Best wishes. (More)

Question

Updated 12/24/2014 11:56:02 PM

1 Answer/Comment

Which of the following is the general form of the equation 5x 2 - 20x = 15?
x 2 - 4x = 3
x 2 - 4x - 3 = 0
5x 2 - 20x - 15 = 0 **Weegy:** Please clarify your question. (More)

Question

Updated 11/26/2014 6:01:20 PM

1 Answer/Comment

The general form of the equation 5x^2 - 20x = 15 is 5x^2 - 20x - 15 = 0 .

Added 11/26/2014 6:01:18 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/27/2014 4:17:20 AM], Rated good by andrewpallarca

An object is dropped off a building that is 144 feet tall. After how many seconds does the object hit the ground? (s = 16t 2)
3 seconds
4 seconds
9 seconds **Weegy:** 16t^2 = 144
Simplify, divide both sides by 16
t^2 = 9
t = 3 seconds **User:** The square of a number exceeds that number by 12. What are the two possible solutions?
3 or -4
3 or 4
-3 or 4 **User:** Which of the following equations is quadratic?
x(x2 + 1) = 0
5(4x + 2) = 3
(x + 3)(x + 4) = 5 **Weegy:** x2- 1 = 0 **User:** What is the solution set of (3x - 1)2 = 5?
**User:** If (x + 5)(x - 2) = 18, then which of the following statements is true?
x + 7 = 0 or x - 4 = 0
x + 5 = 0 or x - 2 = 0
x + 5 = 6 or x - 2 = 3 **Weegy:** 4(x - 3) - 2(x - 1) > 0 4x - 12 - 2x - 2 > 0; 2x - 10 > 0; 2x > 10; x > 10/2; x > 5 **User:** The width and the length of a rectangle are consecutive even integers. If the width is decreased by 3 inches, then the area of the resulting rectangle is 24 square inches. What is the area of the original rectangle?
12 square inches
48 square inches
96 square inches **Weegy:** The width and the length of a rectangle are consecutive even integers. If the width is decreased by 3 inches, then the area of the resulting rectangle is 24 square inches. What is the area of the original rectangle? B. [ 48 square inches
] (More)

Question

Updated 11/26/2014 6:33:49 PM

2 Answers/Comments

If (x + 5)(x - 2) = 18, then the statements of x + 7 = 0 or x - 4 = 0 is true .

(x + 5)(x - 2) = 18

x^2 + 5x - 2x - 10 = 18

x^2 + 3x - 28 = 0

x^2 + 7x - 4x - 7*4 = 0

(x + 7)(x - 4) = 0

So x + 7 = 0 , or x - 4 = 0

(x + 5)(x - 2) = 18

x^2 + 5x - 2x - 10 = 18

x^2 + 3x - 28 = 0

x^2 + 7x - 4x - 7*4 = 0

(x + 7)(x - 4) = 0

So x + 7 = 0 , or x - 4 = 0

Added 11/26/2014 6:33:37 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/27/2014 8:39:04 AM]

Given: -6x 6}
{x | x -6} **Weegy:**
-6x 36/-6;
x > -6, the solution set is: {x | x > -6}
**User:** Given: 3x 0}
{x | x 1} **User:** Given: -4x/7 > 10.
Choose the solution set.
{x | x -35/2}
{x | x -40/7} **Weegy:** -4x/7 > 10 ;
-4x > 70 ;
4x **User:** Given: 3x -2}
{x | x 2}
**Weegy:**
3x **User:** Given: 15x -3}
{x | x 3}
**Weegy:**
15x **User:** Given: 3x -1/3}
{x | x -3} **Weegy:**
3x < -9;
x < -9/3;
x < -3;
the solution is {x | x < -3}
(More)

Question

Updated 11/28/2014 4:09:06 AM

1 Answer/Comment

3x < 3;

x < 3/3;

x < 1;

the solution is {x | x < 1}

x < 3/3;

x < 1;

the solution is {x | x < 1}

Added 11/28/2014 4:09:06 AM

This answer has been confirmed as correct and helpful.

Which of the following is the general form of the equation 5x 2 - 20x = 15?
x 2 - 4x = 3
x 2 - 4x - 3 = 0
5x 2 - 20x - 15 = 0 **Weegy:** The general form of the equation 5x^2 - 20x = 15 is 5x^2 - 20x - 15 = 0 (More)

Question

Expert Answered

Updated 11/26/2014 8:31:00 AM

0 Answers/Comments

34,469,103

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 842 [Total 6715] Ratings 19 Comments 652 Invitations 0 Online

There are no comments.